Pipeline Logic and Culpability: Establishing a Continuum of Harm for Sacrifice Zones - Randolph, Ned (Frontiers in Environmental Science, 2021)
This article builds on studies of Energy Sacrifice Zones as a heuristic for areas negatively impacted by fossil fuel industry practices through environmental degradation and/or pollution that harms the health of nearby residents for broader economic gains elsewhere. Environmental justice scholars have since the 1990s identified urban “fence-line” communities where public health and property values are sacrificed by plant emissions. More recent scholarship has identified analogous dispossession in coastal Louisiana, where indigenous and communities of color have suffered from environmental degradation from fossil fuel industry practices that have led to displacement from land loss due to marsh desiccation and sea level rise. Coastal oil and gas operations have left behind thousands of miles of pipelines, canals and subsiding oil fields that have accelerated land loss. This article argues for a continuum of culpability along the physical pipeline supply chain from wellheads to inland petrochemical plants dependent on inexpensive natural gas feedstock. These sites exist as nodes along a single fossil fuel ecology of production and manufactured scarcity through a secondary market of petroleum-based value-added products. Such zones of harm need not be adjacent to one another to be considered logically contiguous and, therefore, subject to the same consideration of restitution as long as they are connected by the material ecology (or infrastructure) of fossil fuel extraction, production and distribution. Such a concept of pipeline culpability would expand geographic designation of Energy Sacrifice Zones based on the production chain of the fossil fuel industry. This zone of harm, once established, could be used to determine restitution to communities bearing the burden of the carbon economy.